Do the ornamented osteoderms influence the heat conduction through the skin? A finite element analysis in Crocodylomorpha. (October 2017) - Clarac, F.; Goussard, F.; Teresi, L.; Buffrénil, Vde.; Sansalone, V.
Abstract: In order to assess the implication of the crocodylomorph ornamented osteoderms on the skin conduction during basking, we have performed three dimensional modeling and finite element analyses on a sample which includes both extant dry bones and well-preserved fossils tracing back to the Early Jurassic. In purpose to reveal the possible implication of the superficial ornamentation on the osteoderm heat conduction, we repeated the simulation on an equivalent set of smoothed 3D-modeled osteoderms. The comparison of the results evidenced that the presence of the apical sculpture has no significant impact on the osteoderm global conduction. Furthermore, as we also aimed to assess the influence of the inner bone porosity on the osteoderm conduction, we modified the heat equation parameters so that the 3D-modeled osteoderms successively score the compact and the cancellous bone properties ( i.e. mass density, heat capacity, thermal conductivity and thermal diffusivity). Finally, we repeated the analyses using the soft-dermis properties which lead to outline that neither the degree of porosity nor the presence of the osteoderms (in itself) significantly modifies the heat conduction through the crocodylomorph skin. Consequently, as hypothesized by previous authors, if the dermal shield happens to be involved into heat capture during basking for crocodylians, this process must mainly rely on a convective effect based on the osteoderm relative degree of vascularization. This last assumption could thus explain why the crocodylians which produce little metabolic heat would carry an entire vascularized osteoderm shield. Highlights: FEA is used to assess the influence of the ornamented osteoderms on the heat conduction through the crocodylians' skin. Heat conduction is neither modified by the presence of an apical ornamentation nor by the variation of inner porosity. The presence of a post-cranial dermal ossification does not significantly impact the skin's global conduction.